Controlled HIV-HCV Viremia and Immune-Reconstitution are Associated with Slow Progression of Liver Disease in Co-infected Hemophilic Patients After 30 Years of Follow-Up - Badano, Maria Noel (2020)
Introduction and aim: Controversial results have been reported about the progressionof liver disease in HIV-HCV coinfected populations. The purpose of this study is to assesslong-term liver disease progression in a group of coinfected patients with hemophilia.1.2. Materials and Methods: From 1995 to 2015, liver disease was assessed through enzymelevels, platelet counts, Hepatitis C and HIV viral loads (VL), and CD4+T cell counts. Evolution of the APRI liver index was used to estimate hepatic disease (APRI > 1.0 indicatingsevere fibrosis).1.3. Results: 2005-2015 proportional liver-related mortality was below 17% while AIDSand other causes including hemorrhagic events reached 42% each. APRI index >1.0 wasfound in 3 of 32 (9%) patients alive, showing significant liver disease after more than 30years of infection. Analyzing the evolution of liver disease markers, liver enzymes increasedsignificantly only in those patients with detectable HIV and /or HCV VL (for AST and ALT,p<0.0001; for GGT, p=0.001). HIV suppression and reconstitution of CD4+T cell countswere required to achieve HCV eradication. Through multivariate logistic regression, pre ART(pre-antiretroviral therapy) HIV VL was associated with the development of liver fibrosis(OR=4.755; IC95: 1.057 21.387) and with altered liver enzyme values (OR=4.091; IC95:1.293 ? 12.947). No persistent increase in enzyme levels or APRI index was observed in thegroup controlling HIV and HCV replication and adequate immune recovery.1.4. Conclusions: The suppression of both viruses, HIV and HCV, together with adequateimmune recovery is associated with minimal or slow progression of liver disease.